Hollow porous hydrogenation catalyst, preparation method and application thereof, magnetic hollow porous hydrogenation catalyst and application thereof
By preparing the catalyst catalyst in the medium -to -porous hydrogen, the unique pore structure and the pH site are used to solve the problem of low catalyst catalytic activity, and the efficient transformation and catalytic stability of biological aldehyde compounds are realized.
Patent Information
- Application Number
- CN202411471392.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-24
AI Technical Summary
Existing catalysts have low catalytic activity in the MPV reaction of catalytic aldehyde compounds, making it difficult to meet the demand for efficient conversion of biomass aldehyde compounds.
Using hollow porous hydrogenation catalysts, the self-stable precipitation agglomeration, co-agglomeration growth, hydrolysis and saponin of the Malayside-styrene clustering microspheres, combined with soluble salt to perform hydrophilic reactions to form a catalyst with unique pore structure Essence
It improves the catalytic activity, promotes the interaction and mass transfer between substrates and acid-base sites, enhances the efficient CTH conversion ability of carbonyl compounds, and has strong versatility and stability.
Smart Images

Figure CN119346174A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic materials, and in particular to a hollow porous hydrogenation catalyst and a preparation method and application thereof, and a magnetic hollow porous hydrogenation catalyst and application thereof. Background Art
[0002] Faced with increasingly severe environmental problems such as energy crisis, global warming, and severe environmental pollution, the utilization and conversion of lignocellulosic biomass has developed rapidly in recent years. Converting lignocellulosic biomass into other usable biofuels and green chemicals is an important way to solve environmental problems. In recent years, catalytic conversion of biomass such as furfural (FAL), 5-hydroxymethylfurfural (5-HMF), levulinic acid, glycerol, sorbitol, xylitol, etc. has attracted special attention. Furfural contains C=O, C=C, and CO bonds, which makes it highly reactive. Therefore, furfural can be converted into other high value-added products through various pathways. Among them, the selective reduction of furfural to furfuryl alcohol (FOL) is of great significance in biomass conversion, because furfuryl alcohol is an important organic chemical raw material and is widely used in synthetic lubricants, liquid fuels, plastics, resins, fine chemicals and other products.
[0003] Catalytic transfer hydrogenation (CTH) is an attractive strategy for reducing biomass aldehydes using organic hydrogen donors such as alcohols and formic acid instead of hazardous gaseous hydrogen. Compared with corrosive formic acid, the use of alcohols as hydrogen donors and solvents has significant advantages such as low cost, abundant sources, and easy storage and removal. The Meerwein Ponndorf Verley (MPV) reaction is an ideal method for the reduction of carbonyl compounds because it uses large amounts of safe secondary alcohols as hydrogen donors. In recent years, catalysts based on Fe, Al, Co, Cu, Zr, Hf, Pd, etc. have been widely used in MPV reduction. Among them, Zr and Hf, as catalytic active centers, show good catalytic performance for the MPV reaction of aldehydes, but there is still a problem of low catalytic activity. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a hollow porous hydrogenation catalyst and a preparation method and application thereof, a magnetic hollow porous hydrogenation catalyst and application thereof. The hollow porous hydrogenation catalyst prepared by the present invention has high catalytic activity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a hollow porous hydrogenation catalyst, comprising the following steps:
[0007] The maleic anhydride, styrene, an initiator and an organic solvent are mixed to perform self-stabilizing precipitation polymerization to obtain maleic anhydride-styrene copolymer microspheres;
[0008] The maleic anhydride-styrene copolymer microspheres, divinylbenzene, an initiator and an organic solvent are mixed for copolymerization growth to obtain pMS@pDMH microspheres;
[0009] The pMS@pDMH microspheres are dispersed in acetone to remove the inner core and obtain hollow microspheres;
[0010] dispersing the hollow microspheres in an inorganic alkaline solution for hydrolysis and saponification to obtain carboxyl functionalized microspheres;
[0011] The carboxyl functionalized microspheres, soluble zirconium salt and solvent are mixed and subjected to hydrothermal reaction to obtain the hollow porous hydrogenation catalyst.
[0012] Preferably, the molar ratio of maleic anhydride to styrene is 2-5:1-3.
[0013] Preferably, the temperature of the self-stabilizing precipitation polymerization is 75-90° C. and the time is 1-2 hours.
[0014] Preferably, the mass ratio of the maleic anhydride-styrene copolymer microspheres to divinylbenzene is 1.5:5-10.
[0015] Preferably, the copolymerization growth temperature is 75-90° C. and the time is 3-5 hours.
[0016] Preferably, the mass ratio of the carboxyl functionalized microspheres to the soluble zirconium salt is 0.15-0.6:1.5-2.
[0017] The present invention also provides a hollow porous hydrogenation catalyst prepared by the preparation method described in the above technical solution.
[0018] The present invention also provides the use of the hollow porous hydrogenation catalyst described in the above technical solution in catalytic transfer hydrogenation reaction.
[0019] The present invention also provides a magnetic hollow porous hydrogenation catalyst, which is prepared by a method comprising the following steps:
[0020] The amino-modified Fe3O4 nanoparticles, the hollow porous hydrogenation catalyst described in the above technical solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and a solvent are mixed for condensation reaction to obtain the magnetic hollow porous hydrogenation catalyst.
[0021] The present invention also provides the use of the magnetic hollow porous hydrogenation catalyst described in the above technical solution in catalytic transfer hydrogenation reaction.
[0022] The invention provides a method for preparing a hollow porous hydrogenation catalyst, comprising the following steps: mixing maleic anhydride, styrene, an initiator and an organic solvent for self-stabilizing precipitation polymerization to obtain maleic anhydride-styrene copolymer microspheres; mixing the maleic anhydride-styrene copolymer microspheres, divinylbenzene, an initiator and an organic solvent for copolymerization growth to obtain pMS@pDMH microspheres; dispersing the pMS@pDMH microspheres in acetone to remove the inner core to obtain hollow microspheres; dispersing the hollow microspheres in an inorganic alkaline solution for hydrolysis and saponification to obtain carboxyl functionalized microspheres; mixing the carboxyl functionalized microspheres, a soluble zirconium salt and a solvent for hydrothermal reaction to obtain the hollow porous hydrogenation catalyst. In the present invention, maleic anhydride (MAH) and styrene (St) are firstly prepared by self-stabilizing precipitation polymerization to obtain pMS microspheres, divinylbenzene (DVB) and maleic anhydride monomers are copolymerized and grown on the surface of the pMS microspheres to form pMS@pDMH microspheres with a core-shell structure wrapped by a divinylbenzene and maleic anhydride copolymer (poly(divinylbenzene-maleic anhydride), pDMH), the pMS@pDMH microspheres are treated with acetone to remove the pMS core to obtain hollow microspheres (hollowpDMH microspheres, h-pDMH), the maleic anhydride groups contained in the h-pDMH are converted into maleic acid by hydrolysis and saponification to obtain carboxyl functionalized microspheres, the carboxyl functionalized microspheres are hollow styrene maleic acid copolymer spherical shell microspheres (hollow poly(divinylbenzene-maleic acid)microspheres, h-pDMA), and under hydrothermal conditions, the carboxyl groups contained in the h-pDMA react with Zr 4+ Coordination is performed to obtain the hollow porous hydrogenation catalyst (hollow zirconium coordination polymer microspheres, h-pDMA&Zr).
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention uses hollow polymer microspheres (h-pDMA) rich in carboxyl groups hydrolyzed from DVB-MAH as organic ligands, and constructs a novel hollow porous zirconium-based acid-base catalyst through a simple self-assembly method. The prepared hollow structure hydrophilic acid-base catalyst has a unique pore structure consisting of a hollow core and a mesoporous shell. The mesopores in the shell can accelerate the mass transfer rate, connect the inside and outside of the hollow core, and provide channels for the free diffusion of reactants and products, respectively. Unlike bulk materials that limit the full contact between active sites and substrates, the hollow structure and large pore size of the hollow porous hydrogenation catalyst of the present invention can promote the interaction and mass transfer between substrates and acid-base sites, thereby improving the reaction activity. Moreover, h-pDMA&Zr also shows strong versatility in the reduction reaction of different carbonyl compounds, and can be used for efficient CTH conversion of many carbonyl compounds, and will have great potential to produce valuable chemicals through CTH.
[0025] The present invention also provides a magnetic hollow porous hydrogenation catalyst (mh-pDMA&Zr), which is obtained by covalently connecting amino-modified Fe3O4 nanoparticles (nanoparticles, NPs) with the carboxyl groups of h-pDMA&Zr. mh-pDMA&Zr not only has a hollow mesoporous structure, abundant acid-base sites and good hydrophilicity, but also has magnetic recovery performance.
[0026] The data of the embodiment show that the magnetic hollow porous hydrogenation catalyst of the present invention has a high catalytic activity. Under the conditions of 120°C and 2h, the conversion rate of iPrOH is 99.8% and the yield is 99.1%. It can be used for at least five reactions without significantly reducing the catalytic activity. After the reaction is completed, the catalyst can be separated by an external magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a flow chart for the preparation of h-pDMA&Zr and mh-pDMA&Zr in Example 1;
[0028] Figure 2 The SEM and TEM characterization images of the products in each step of Example 1;
[0029] Figure 3 (a) is the infrared spectra of h-pDMH, h-pDMA, h-pDMA&Zr and mh-pDMA&Zr, (b) is the XRD spectra of h-pDMA, h-pDMA&Zr and mh-pDMA&Zr;
[0030] Figure 4 N2 adsorption / desorption isotherms of h-pDMA and h-pDMA&Zr;
[0031] Figure 5is the pore size distribution diagram of h-pDMA and h-pDMA&Zr;
[0032] Figure 6 HAADF-STEM image and element distribution of h-pDMA&Zr;
[0033] Figure 7 NH3-TPD images of ZrO2 and h-pDMA&Zr;
[0034] Figure 8 CO2-TPD images of ZrO2 and h-pDMA&Zr;
[0035] Fig. 9 is the infrared spectrum of pyridine;
[0036] Fig.10 It is the full scan spectrum of h-pDMA&Zr;
[0037] Fig.11 is the Zr 3dXPS spectrum;
[0038] Fig.12 is the O1s XPS spectrum;
[0039] Fig.13 is the recycling curve of mh-pDMA&Zr;
[0040] Fig.14 is the magnetic curve of mh-pDMA&Zr;
[0041] Fig.15 is the SEM image of the recycled mh-pDMA&Zr;
[0042] Fig.16 is the XRD spectrum of the recovered mh-pDMA&Zr;
[0043] Fig.17 is the Zr 3dXPS spectrum of the recovered mh-pDMA&Zr;
[0044] Fig.18 is the O1s XPS spectrum of the recovered mh-pDMA&Zr;
[0045] Fig.19 This is the effect curve of temperature on the hydrogenation of FAL to produce FOL;
[0046] Fig. 20 This is the effect curve of time on the generation of FOL by hydrogenation of FAL;
[0047] Fig.21 This is the curve showing the effect of catalyst dosage on the hydrogenation of FAL to produce FOL;
[0048] Fig. 22 This is the curve showing the effect of alcohol type on the hydrogenation of FAL to produce FOL. DETAILED DESCRIPTION
[0049] The present invention provides a method for preparing a hollow porous hydrogenation catalyst, comprising the following steps:
[0050] The maleic anhydride, styrene, an initiator and an organic solvent are mixed to perform self-stabilizing precipitation polymerization to obtain maleic anhydride-styrene copolymer microspheres;
[0051] The maleic anhydride-styrene copolymer microspheres, divinylbenzene, an initiator and an organic solvent are mixed for copolymerization growth to obtain pMS@pDMH microspheres;
[0052] The pMS@pDMH microspheres are dispersed in acetone to remove the inner core and obtain hollow microspheres;
[0053] dispersing the hollow microspheres in an inorganic alkaline solution for hydrolysis and saponification to obtain carboxyl functionalized microspheres;
[0054] The carboxyl functionalized microspheres, soluble zirconium salt and solvent are mixed and subjected to hydrothermal reaction to obtain the hollow porous hydrogenation catalyst.
[0055] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0056] The invention mixes maleic anhydride, styrene, an initiator and an organic solvent to carry out self-stabilizing precipitation polymerization to obtain maleic anhydride-styrene copolymer microspheres.
[0057] In the present invention, the molar ratio of maleic anhydride to styrene is preferably 2-5:1-3, specifically 2:1.
[0058] In the present invention, the initiator is preferably azobisisobutyronitrile.
[0059] In the present invention, the molar ratio of maleic anhydride to initiator is preferably 2-5:0.002-0.004.
[0060] In the present invention, the organic solvent is preferably isoamyl acetate.
[0061] In the present invention, the usage ratio of maleic anhydride to isoamyl acetate is preferably 0.2-0.5 mol:150-300 mL, and specifically can be 0.25 mol:250 mL.
[0062] In the present invention, the temperature of the self-stabilizing precipitation polymerization is preferably 75 to 90° C., specifically 75, 80, 85 or 90° C., and the time is preferably 1 to 2 hours.
[0063] The present invention preferably adds maleic anhydride, styrene, azobisisobutyronitrile and isoamyl acetate into a single-necked flask, completely dissolves the maleic anhydride and the initiator by ultrasound, then deoxygenates the obtained mixture by nitrogen bubbling for 0.5 to 1 hour, and then performs the self-stabilizing precipitation polymerization to obtain the pMS microspheres, i.e., monodisperse poly(MAH-alt-St) microspheres, which are directly used to prepare core-shell particles.
[0064] After obtaining the maleic anhydride-styrene copolymer microspheres, the present invention mixes the maleic anhydride-styrene copolymer microspheres, divinylbenzene, an initiator and an organic solvent for copolymerization growth to obtain pMS@pDMH microspheres.
[0065] In the present invention, the mass ratio of the maleic anhydride-styrene copolymer microspheres to divinylbenzene is preferably 1.5:5-10, and specifically may be 1.5:9.
[0066] In the present invention, the initiator is preferably azobisisobutyronitrile.
[0067] In the present invention, the mass ratio of divinylbenzene to initiator is preferably 5-10:0.02-0.06, and specifically may be 9:0.05.
[0068] In the present invention, the organic solvent is preferably n-heptane.
[0069] In the present invention, the usage ratio of divinylbenzene to n-heptane is preferably 5-10 g:125 mL, specifically 9 g:125 mL.
[0070] In the present invention, the copolymerization growth temperature is preferably 75-90° C., specifically 75, 80, 85 or 90° C., and the time is preferably 3-5 h, specifically 3, 4 or 5 h.
[0071] The present invention preferably adds divinylbenzene, n-heptane and azobisisobutyronitrile to the dispersion of pMS particles to carry out the copolymerization growth, and obtains the MS@pDMH microspheres by centrifugal separation, which are core-shell particles.
[0072] After obtaining the MS@pDMH microspheres, the present invention disperses the pMS@pDMH microspheres in acetone to remove the core, thereby obtaining hollow microspheres.
[0073] In the present invention, the number of dispersions is preferably 3 to 5 times, and the time for each dispersion is preferably 0.5 h.
[0074] The present invention preferably disperses the MS@pDMH microspheres in acetone, stirs for 0.5 h, then centrifuges to remove the dissolved pMS core, repeats the denuclearization process 3 to 5 times, obtains the hollow microspheres, i.e., anhydride functionalized h-pDMH, and dries in a vacuum drying oven for later use. The present invention does not specifically limit the specific parameters of the drying, and parameters familiar to those skilled in the art can be used.
[0075] After the hollow microspheres are obtained, the present invention disperses the hollow microspheres in an inorganic alkaline solution for hydrolysis and saponification to obtain carboxyl functionalized microspheres.
[0076] In the present invention, the inorganic alkaline solution is preferably a sodium hydroxide aqueous solution, and the concentration of the sodium hydroxide aqueous solution is preferably 0.1 mol / L.
[0077] In the present invention, the usage ratio of the hollow microspheres to the sodium hydroxide aqueous solution is preferably 6 g:100 mL.
[0078] In the present invention, the temperature of the hydrolysis and saponification is preferably room temperature, and the time is preferably 6 hours.
[0079] In the present invention, the hydrolysis and saponification are preferably carried out under stirring conditions, and the stirring speed is preferably 500 rpm.
[0080] The present invention preferably disperses h-pDMH in a sodium hydroxide aqueous solution for the hydrolysis and saponification, then separates the reaction product by centrifugation, washes it with deionized water and ethanol, and dries it under reduced pressure at 45° C. for 24 hours to obtain carboxyl functionalized microspheres.
[0081] After obtaining the carboxyl functionalized microspheres, the present invention mixes the carboxyl functionalized microspheres, a soluble zirconium salt and a solvent to carry out a hydrothermal reaction to obtain the hollow porous hydrogenation catalyst.
[0082] In the present invention, the mass ratio of the carboxyl functionalized microspheres to the soluble zirconium salt is preferably 0.15-0.6:1.5-2, specifically 0.15:1.5, 0.3:1.5 or 0.6:1.5.
[0083] In the present invention, the soluble zirconium salt is preferably ZrCl4.
[0084] The present invention preferably disperses h-pDMA (0.6 g) in deionized water (20 mL), disperses ZrCl4 (1.5 g) in N,N-dimethylformamide (DMF), then drops the ZrCl4 solution into the h-pDMA dispersion, and then reacts in a hydrothermal autoclave for 10 hours, and then the obtained product is filtered, washed and dried in sequence to obtain the hollow porous hydrogenation catalyst.
[0085] The present invention also provides a hollow porous hydrogenation catalyst prepared by the preparation method described in the above technical solution.
[0086] The present invention also provides the use of the hollow porous hydrogenation catalyst described in the above technical solution in catalytic transfer hydrogenation reaction.
[0087] In the present invention, the catalytic transfer hydrogenation reaction preferably includes a furfural hydrogenation reaction.
[0088] In the present invention, the temperature of the furfural hydrogenation reaction is preferably 100-140°C, specifically 100, 110, 120, 130 or 140°C, and the time is preferably 0.5-2.5h, specifically 0.5, 1, 1.5, 2 or 2.5h.
[0089] In the present invention, during the furfural hydrogenation reaction, the usage ratio of furfural to catalyst is preferably 1 mmol:25-125 mg, specifically 1 mmol:25 mg, 1 mmol:50 mg, 1 mmol:75 mg, 1 mmol:100 mg or 1 mmol:125 mg.
[0090] In the present invention, the furfural hydrogenation reaction is preferably carried out in an alcohol solvent, and the usage ratio of furfural to alcohol solvent is preferably 1 mmol:5 mL.
[0091] In the present invention, the alcohol solvent is preferably methanol, ethanol, n-propanol, n-butanol or isopropanol.
[0092] The present invention also provides a magnetic hollow porous hydrogenation catalyst, which is prepared by a method comprising the following steps:
[0093] The amino-modified Fe3O4 nanoparticles, the hollow porous hydrogenation catalyst described in the above technical solution, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC·HCl), N-hydroxysuccinimide (NHS) and a solvent are mixed for condensation reaction to obtain the magnetic hollow porous hydrogenation catalyst.
[0094] In the present invention, the amino-modified Fe3O4 nanoparticles are preferably prepared by a method comprising the following steps:
[0095] Fe3O4 nanoparticles (Fe3O4 NPs) are dispersed in an organic solvent and heated. When the reaction temperature rises to 60°C, aminopropyltriethoxysilane is injected into the dispersion under stirring to react. The product is collected, washed and dried to obtain the amino-modified Fe3O4 nanoparticles.
[0096] In the present invention, the particle size of the Fe3O4 nanoparticles is preferably 25 to 50 nm.
[0097] In a specific embodiment of the present invention, the preparation method of the Fe3O4 nanoparticles is as follows: FeCl3·6H2O and FeCl2·4H2O are dissolved in deionized water, N2 is added for 0.5h to deoxygenate the mixture, ammonia water is added under stirring to adjust the pH value of the system to 9, and the reaction is carried out at 60°C for 0.5h. After the reaction is completed, the product is collected, washed three times with ethanol, and dried in a vacuum overnight to obtain the Fe3O4 nanoparticles.
[0098] In the present invention, the organic solvent is preferably anhydrous isopropanol.
[0099] In the present invention, the dosage ratio of the Fe3O4 nanoparticles to anhydrous isopropanol is preferably 1 g:50 mL.
[0100] In the present invention, the dosage ratio of the Fe3O4 nanoparticles to aminopropyltriethoxysilane is preferably 1 g:2 mL.
[0101] In the present invention, the reaction temperature is preferably 60° C. and the reaction time is preferably 10 h.
[0102] The present invention has no particular limitation on the specific manner of washing and drying, and any manner familiar to those skilled in the art may be used.
[0103] In the present invention, the mass ratio of the amino-modified Fe3O4 nanoparticles to the hollow porous hydrogenation catalyst is preferably 1:4.
[0104] In the present invention, the temperature of the condensation reaction is preferably 60° C., and the time is preferably 10 h. During the condensation reaction, the carboxyl groups on the surface of the hollow porous hydrogenation catalyst react with the amino groups of NHS to form amide bonds.
[0105] The present invention preferably disperses the hollow porous hydrogenation catalyst in deionized water and stirs it, then adds the amino-modified Fe3O4 nanoparticles into a reaction bottle, and after 30 minutes, adds EDC·HCl solution and NHS solution into the reaction bottle at 60° C. at the same time, reacts for 10 hours, and then centrifuges, washes, and dries to obtain the magnetic hollow porous hydrogenation catalyst (mh-pDMA&Zr).
[0106] In the present invention, the concentration of the EDC·HCl solution is preferably 5 mg / mL.
[0107] In the present invention, the usage ratio of the hollow porous hydrogenation catalyst to the EDC·HCl solution is preferably 0.2 g:4 mL.
[0108] In the present invention, the concentration of the NHS solution is preferably 6 mg / mL.
[0109] In the present invention, the usage ratio of the hollow porous hydrogenation catalyst to the NHS solution is preferably 0.2 g:4 mL.
[0110] The present invention has no particular limitation on the specific parameters of the centrifugal washing and drying, and methods well known to those skilled in the art may be used.
[0111] The present invention also provides the use of the magnetic hollow porous hydrogenation catalyst described in the above technical solution in catalytic transfer hydrogenation reaction.
[0112] In the present invention, the catalytic transfer hydrogenation reaction preferably includes a furfural hydrogenation reaction.
[0113] The present invention has no special limitation on the parameters of the furfural hydrogenation reaction, and the parameters described in the above technical solution can be adopted, which will not be repeated here.
[0114] In the present invention, the magnetic hollow porous hydrogenation catalyst is preferably reused after use, and the reuse preferably includes the following steps: after the catalytic transfer hydrogenation reaction is completed, the mh-pDMA&Zr is separated from the reaction mixture by an external magnet, and then washed with isopropanol (2-PrOH) for 3 to 5 times, and dried at 80°C for 8 hours under vacuum to obtain a fresh magnetic hollow porous hydrogenation catalyst.
[0115] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0116] The raw materials and equipment used in the present invention are shown in Tables 1-2.
[0117] Table 1 Main raw materials
[0118] Reagents English factory Specification Styrene Styrene(St) Aladdin Analytical grade Maleic anhydride Maleicanhydride(MAH) AlfaAesar Analytical grade Isoamyl acetate Isoamylacetate Tianjin Fuchen Chemical Reagent Factory Analytical grade N,N-Dimethylformamide DMF Sinopharm Group Analytical grade Divinylbenzene Divinylbenzene (DVB) AlfaAesar Analytical grade Ferrous chloride tetrahydrate <![CDATA[FeCl2·4H2O]]> AlfaAesar Analytical grade n-Heptane n-Heptane Tianjin Fuchen Chemical Reagent Factory Analytical grade Furfural Furfural(FAL) Sigma-Aldric Analytical grade Deionized water <![CDATA[H2O]]> Laboratory-made / Zirconium chloride <![CDATA[ZrCl4]]> Sinopharm Group Analytical grade N-Hydroxysuccinimide NHS AlfaAesar Analytical grade Ferric chloride hexahydrate <![CDATA[FeCl3·6H2O]]> AlfaAesar Analytical grade hydrochloric acid HCl Beijing Chemical Reagents Analytical grade acetone Acetone Beijing Ruixiang Nengyuan Trading Analytical grade Sodium hydroxide NaOH AlfaAesar Analytical grade Petroleum ether Petroleumether Tianjin Fuchen Chemical Reagent Factory Analytical grade Ethanol Ethanol Tianjin Fuchen Chemical Reagent Factory Analytical grade Azobisisobutyronitrile AIBN Aladdin Analytical grade
[0119] Table 2 Main equipment
[0120]
[0121]
[0122] Scanning electron microscopy (SEM): The morphology of the materials was tested by scanning electron microscopy (SU8020, accelerating voltage: 15 kV).
[0123] X-ray diffraction (XRD): The crystal structure of the material was tested and analyzed by a powder diffractometer (X'PertPRO MPD). The diffractometer used a copper target, 40 kV operating voltage, and a scanning rate of 1° / min.
[0124] X-ray Photoelectron Spectroscopy (XPS): The element content, valence state and chemical bond type of the material were tested using an X-ray photoelectron spectrometer (Thermo VG ESCALAB250).
[0125] Fourier transform infrared spectroscopy (FTIR): A Bruker Tensor 27 FTIR analyzer was used to test the functional groups of the materials.
[0126] Nitrogen adsorption and desorption: The material nitrogen adsorption and desorption test uses a physical adsorption instrument (Micromeritics ASAP2020V3.01H). The sample is placed in a vacuum environment at 150°C and pretreated for 4 hours. Subsequently, the specific surface area, pore size and other properties of the material are tested.
[0127] Inductively coupled plasma spectroscopy (ICP): Agilent ICPMS7800 equipment was used to quantitatively analyze the Zr content in the samples.
[0128] Pyridine infrared spectroscopy (py-FTIR): A Nicolet 380 FTIR spectrometer was used to detect the Lewis acid and Acid sites. The following formula is used to calculate Acid sites (N BAS ) and Lewis acid sites (N LAS ) quantity.
[0129] N BAS =1.88×IA B ×R 2 / W
[0130] N LAS =1.42×IA L ×R 2 / W
[0131] In the formula, IA B IA L , R and W are 1540cm -1 and 1445cm -1 The adsorption zone at , the radius and weight of the sample pan used.
[0132] Ammonia temperature-programmed desorption (NH3-TPD): The chemical adsorption analyzer Auto ChemII 2920 was used to characterize the material samples by NH3-TPD to determine the number and distribution of acidic sites.
[0133] Carbon dioxide temperature programmed desorption (CO2-TPD): The number and distribution of basic sites were determined by CO2-TPD characterization of material samples using a chemical adsorption analyzer Auto ChemII 2920.
[0134] Example 1
[0135] The preparation process of mh-pDMA&Zr is as follows Figure 1 As shown, the specific method is as follows:
[0136] 1. Preparation of pMS
[0137] MAH (0.25 mol), St (0.125 mol) and AIBN (2.28 mmol) and 250 mL of isoamyl acetate were added to a single-necked flask. MAH and AIBN were completely dissolved by ultrasound, and then the mixture was deoxygenated by nitrogen bubbling for 0.5 h. Then, self-stabilized precipitation polymerization was carried out at 75 ° C for 2 h to obtain monodisperse poly (MAH-alt-St) (pMS) microspheres and directly used to prepare core-shell particles.
[0138] 2. Preparation of h-pDMH
[0139] DVB (9 g), n-heptane (125 mL), and AIBN (0.05 g) were added to the dispersion of pMS particles (1.5 g), stirred (500 rpm) at 75 ° C for 3 h, and the core-shell particles were prepared by centrifugation. The prepared core-shell particles were dispersed in 300 mL of acetone, stirred for 30 min, and then centrifuged to remove the dissolved pMS core. The core removal process was repeated 3 times to obtain anhydride functionalized h-pDMH, which was dried in a vacuum drying oven for use.
[0140] 3. Preparation of h-pDMA
[0141] h-pDMH (6 g) was dispersed in 0.1 mol / L sodium hydroxide aqueous solution (100 mL). The hydrolysis and saponification reactions were carried out at room temperature with a stirring speed of 500 rpm. After 6 h, the reaction product was separated by centrifugation and washed with deionized water and ethanol. After drying under reduced pressure at 45 °C for 24 h, carboxyl functionalized h-pDMA was finally obtained.
[0142] 4. Preparation of h-pDMA&Zr
[0143] h-pDMA (0.6 g) and 1.5 g ZrCl4 were dispersed in 20 mL deionized water and 20 mL DMF, respectively, and stirred at room temperature for 15 min. Then, the ZrCl4 solution was added dropwise into the h-pDMA solution. Then, the reaction was carried out in a hydrothermal reactor for 10 h. Finally, the product was filtered, washed, and dried to obtain the catalyst h-pDMA&Zr (also recorded as h-pDMA&Zr-1).
[0144] 5. Preparation of amino-modified Fe3O4 nanoparticles
[0145] FeCl3·6H2O and FeCl2·4H2O were dissolved in deionized water. N2 was added for 0.5h to deoxygenate the mixture, and ammonia was added to adjust the pH of the system to 9 under stirring conditions. The reaction was carried out at 60℃ for 0.5h. After the reaction was completed, the product was collected and washed three times with ethanol. After drying overnight in a vacuum, Fe3O4 NPs (particle size 25-50nm) were obtained. Fe3O4 NPs (1g) were added to a three-necked flask containing 50mL of anhydrous isopropanol. When the reaction temperature was increased to 60℃, APTES (2mL) was injected into the reaction solution under vigorous stirring. After reacting for 10h, the product was collected. After multiple washings and drying, amino-modified Fe3O4 NPs were obtained.
[0146] 6. Preparation of mh-pDMA&Zr
[0147] 200 mg of h-pDMA&Zr was dispersed in 20 mL of deionized water and stirred. Then, 50 mg of amino-modified Fe3O4NPs was added to the reaction bottle. After 30 min, 4 mL of EDC·HCl solution (5 mg / mL) and 4 mL of NHS solution (6 mg / mL) were added to the reaction bottle at 60 °C. After 10 h of reaction, the mixture was centrifuged, washed and dried to obtain magnetic hollow polymer microspheres mh-pDMA&Zr.
[0148] 7. Catalytic furfural hydrogenation experiment
[0149] Furfural (1 mmol) was dissolved in 5 mL of isopropanol (2-propanol), and then a certain amount of catalyst was added. The reduction reaction was carried out in a 10 mL stainless steel autoclave. After the reaction was completed according to the preset conditions, the reaction solution was centrifuged to separate the catalyst, and the supernatant was taken for quantitative analysis. Catalyst recovery steps: After each reaction, the catalyst in the reaction solution was thoroughly washed with ether by centrifugation and vacuum dried at 80°C for 12 hours. In the leaching test, the h-pDMA&Zr catalyst was separated from the reaction solution by filtration after reacting at 120°C for 1 hour. The remaining solution continued to react for another 1.5 hours.
[0150] Reaction product analysis
[0151] The collected reaction liquid mixture was quantitatively analyzed by gas chromatography (SHIMADZU GC-2014C HP-5MS capillary column, 30m×250μm×0.25μm). The conversion rate of FAL, the yield of FOL and the selectivity of FOL were calculated as follows:
[0152] Furfural conversion rate = molar amount of furfural reacted / initial molar amount of furfural × 100%
[0153] Furfuryl alcohol yield = molar amount of furfuryl alcohol produced / molar amount of initial furfural × 100%
[0154] Furfuryl alcohol selectivity = furfuryl alcohol yield / furfural conversion rate × 100%
[0155] Figure 2 The SEM and TEM characterization images of the products of each step in Example 1, wherein (a) is a TEM image of h-PDMH, (b) is a TEM image of h-pDMA, (c) is a TEM image of h-pDMA&Zr, (d) is a TEM image of mh-pDMA&Zr, (e) is a SEM image of h-PDMH, (f) is a SEM image of h-pDMA, (g) is a SEM image of h-pDMA&Zr, and (h) is a SEM image of mh-pDMA&Zr. Figure 2 The scale bars are all 500nm. Figure 2 As shown in (a), h-PDMH particles are composed of hollow microspheres with an average diameter of 900 nm. Figure 2 As can be seen in (b), the morphology of h-pDMA particles did not change after hydrolysis, indicating that the cross-linked shell has high strength. However, the particle diameter increased slightly, which may be due to the swelling of the hollow microspheres caused by hydrolysis and the conversion of a large number of anhydride groups on the surface of the microspheres to carboxyl groups. After hydrothermal coordination with zirconium, the shell surface of h-pDMA&Zr became rough and the diameter decreased slightly. After access to Fe3O4, the SEM image of mh-pDMA&Zr is shown in Figure 2. Figure 2 As shown in (d). Fe3O4 nanoparticles are distributed on the surface of the spherical shell. Figure 2 The TEM image in (h) also confirms this phenomenon. Figure 6 The HAADF-STEM image and element distribution of h-pDMA&Zr show that Zr, O, and C are evenly distributed, indicating that Zr 4+ It was successfully introduced and evenly dispersed in mh-pDMA&Zr. ICP-AES determined that the content of Zr in mh-pDMA&Zr was 30.3wt% and the content of Fe was 3.8wt%.
[0156] Infrared:
[0157] The infrared spectra of h-pDMH, h-pDMA, h-pDMA&Zr and mh-pDMA&Zr are shown in Figure 3 In the unhydrolyzed h-pDMH, 1850cm -1 and 1778cm -1 The peaks at 1223 cm-1 are the asymmetric stretching vibration and symmetric stretching vibration of C=O in maleic anhydride. -1 and 1076cm -1 The stretching vibrations of the CO and COC bonds on the anhydride rings are respectively, which proves the presence of maleic anhydride in h-pDMH. Due to the presence of crosslinking agent divinylbenzene (DVB), 1496 cm -1 and 1600cm -1 The peaks at 1858cm and 1860cm are the vibrations of the benzene ring skeleton in the divinylbenzene monomer. After hydrolysis, the typical characteristic peaks of h-pDMH (1858cm -1 and 1778cm -1 ) disappears, and at the same time, a new peak appears at 1577 cm -1 and 1395cm -1 1715cm -1 The peak at 1715cm is the stretching vibration of C=O in the free carboxylic acid, which proves that the anhydride is successfully hydrolyzed to carboxyl, and then hydrothermally coordinated with ZrCl4 to form h-pDMA&Zr. Compared with h-pDMA, -1 The free carboxylic acid peak at 1588 cm -1 and 1372cm -1 The peaks at correspond to the asymmetric vibration and symmetric vibration of -CO2- in the monodentate coordination (Vas-Vs=216>200cm -1 ), therefore, in h-pDMA&Zr, the coordination mode between carboxylate and Zr is monodentate. -1 , 655cm -1 and 465cm -1 The peaks at the bottom are all Zr-O stretching vibrations. 4+ After loading with ferroferric oxide, the IR spectrum of mh-pDMA&Zr is 584cm -1 The peak at 1640-1560 cm-1 indicates the stretching vibration of the Fe-O bond, which only exists in Fe3O4 nanoparticles. This proves that Fe3O4 is successfully loaded. However, the characteristic peaks of the newly formed amide bond (formed by the reaction of the amino group in the amino-modified Fe3O4 NPs with the carboxyl group in h-pDMA&Zr) are at 1640-1560 cm-1. -1 Merge with other peaks in the range.
[0158] XRD:
[0159] Figure 3 (b) shows the XRD spectra of h-pDMA, h-pDMA&Zr and mh-pDMA&Zr. Among them, h-pDMA shows a broad diffraction peak, indicating that h-pDMA is in an amorphous state. After hydrothermal coordination with Zr, h-pDMA&Zr does not show any new diffraction peaks, proving that there is no hydrothermal process and no zirconium dioxide is formed, and it is still in an amorphous state. Compared with h-pDMA&Zr, mh-pDMA&Zr shows diffraction peaks of ferroferric oxide, with peak values of 30.2, 35.6, 43.3, 53.5, 57.1 and 62.7, corresponding to the (220), (311), (400)(422)(511) and (440) crystal planes of ferroferric oxide, respectively, indicating that Fe3O4 has been successfully introduced into mh-pDMA&Zr. In addition, the crystal planes of Fe3O4 can be clearly observed in the high-resolution (HR) TEM images, which is consistent with the XRD analysis results.
[0160] BET:
[0161] The N2 adsorption / desorption isotherms of h-pDMA and h-pDMA&Zr are shown in Figure 4 As shown in the figure, according to the IUPAC classification, they are all type II isotherms. At low and medium relative pressures (0-0.8), the N2 absorption increases slowly without hysteresis. At higher relative pressures, the N2 absorption of the isotherm increases rapidly, reflecting the characteristics of mesopores and macropores in the material. Figure 5 From the pore size distribution, it can be seen that the BJH pore size distribution curves of h-pDMA and h-pDMA&Zr show a hierarchical pore characteristic consisting of mesopores less than 3.5nm and meso-macropores greater than 3.5nm. It is worth noting that the specific surface area of h-pDMA&Zr after coordination (22.1m 2 / g) is higher than h-pDMA (5.2m 2 / g), which is due to the rough surface of h-pDMA&Zr, which can significantly improve the adsorption capacity of nitrogen. However, the average pore size of h-pDMA&Zr (10.4nm) is slightly smaller than that of h-pDMA (11.2nm), indicating that the carboxyl group and Zr 4+ The coordination effect also occurs in the internal channels of h-pDMA, resulting in a decrease in the average pore size.
[0162] The specific surface area of mh-pDMA & Zr after the incorporation of Fe3O4 (82.7 m 2 / g) and pore size (17.2nm) are significantly increased, which is provided by the Fe3O4 accessed on the surface.
[0163] Acidity and alkalinity: TPD+XPS
[0164] The acid-base properties of h-pDMA, Zr and ZrO2 were studied by NH3-TPD and CO2-TPD characterization methods (programmed temperature adsorption and desorption). Figures 7-8 As shown, Figure 7 NH3-TPD images of ZrO2 and h-pDMA&Zr. Figure 8 The CO2-TPD images of ZrO2 and h-pDMA&Zr. The larger the NH3 / CO2 desorption amount, the higher the desorption temperature, indicating that the catalyst surface has more or stronger acid-base sites. It can be seen that h-pDMA&Zr has a higher acid-base site content than ZrO2. This is because the carboxyl groups in h-pDMA&Zr react with Zr during the hydrothermal treatment. 4+ The coordination between them builds a -CO-Zr-OC- framework, thus forming a Lewis acid site (Zr 4+ ) and basic sites (O2 - ).
[0165] Learn more about Lewis and The acidic sites were investigated by FT-IR spectroscopy of pyridine adsorption on the catalysts under vacuum conditions at two desorption temperatures, 150 °C and 250 °C. Fig. 9 It can be seen that six infrared characteristic bands appear in h-pDMA&Zr, which are pyridine and Lewis acid sites (1445, 1575, 1607 cm -1 ), Acidic position (1540, 1638cm -1 ) and both acid sites (1490cm -1 ) interaction. According to the -CO-Zr-OC- coordination framework, the Lewis acidic site should come from Zr 4+ , The acid sites should come from the protonated carboxyl groups (-CO2H) or uncoordinated carboxyl groups in hp-DMA. In addition, the quantitative analysis of the surface acid sites showed that the amount of Lewis acid sites of h-pDMA&Zr at 150 °C was 0.043 mmol·g -1 , 0.022mmol·g at 250℃ -1 , 150℃ Acid content: 0.006mmol·g -1 , 0.002mmol·g at 250℃ -1 .
[0166] XPS was used to detect the elemental composition and local environment of ZrO2 and h-pDMA&Zr, and to analyze the strength of their Lewis acidic and Lewis basic sites. Fig.10 The full scan spectrum confirmed the presence of Zr, O, and C in h-pDMA&Zr. From the high-resolution spectrum of Zr ( Fig.11 ) It can be seen that the binding energy of Zr3d in h-pDMA&Zr is higher than that of ZrO2, indicating that Zr in h-pDMA&Zr 4+ It has a higher positive charge, which means a higher Lewis acid strength. Fig.12 The high-resolution spectrum of O1s in h-pDMA&Zr shows that the binding energy of O1s in h-pDMA&Zr shifts from 530.0 to 531.8 eV compared with ZrO2, indicating that O in h-pDMA&Zr has a higher negative charge, which means a lower Lewis base strength. Having a higher acid strength and a lower base strength on the catalyst will be beneficial to the transfer hydrogenation reaction, especially inhibiting the side reactions such as condensation caused by strong alkaline substances. These parameters indicate that h-pDMA&Zr has a higher acid-base synergistic catalytic activity.
[0167] The recyclability of a catalyst is an important indicator for evaluating the catalytic stability of a catalyst, and it is also one of the important indicators for evaluating the application potential of a catalyst in an industrial process. Ferrosilicon is loaded on h-pDMA&Zr through an amide bond to obtain mh-pDMA&Zr. In the cyclic experiment, the reaction conditions are: 1 mmol furfural, 5 mL 2-PrOH (isopropanol), 125 mg catalyst. After each reaction, mh-pDMA&Zr can be separated from the reaction mixture by an external magnet. After the reaction, the catalyst solid was collected by centrifugation, washed three times with 2-PrOH, and dried at 80°C under vacuum for 8 hours. Fig.13 As shown in the figure, after 5 cycles of reaction, the catalytic activity of mh-pDMA&Zr did not decrease significantly, and the FAL conversion rate and FOL yield still reached 96.5% and 95.1%, respectively, indicating that mh-pDMA&Zr exhibited good catalytic stability. The magnetic properties of mh-pDMA&Zr were further tested in the range of -20000 to +20000 Oe. The hysteresis loop of mh-pDMA&Zr is shown in Fig.14 As shown, the maximum saturation magnetic susceptibility (MSMs) is 48.1emu / g. The results show that mh-pDMA&Zr has sensitive magnetic responsiveness, so the catalyst can be separated by an external magnet. From the above analysis, it can be seen that mh-pDMA&Zr has an amorphous mesoporous structure and good thermal stability, which is conducive to the selective synthesis of FOL by FAL through CTH.
[0168] The mh-pDMA&Zr after five cycles were characterized by SEM, XRD, and XPS. Figures 15 to 18As shown, the physicochemical properties of mh-pDMA&Zr, such as morphology, size, and structure, did not change significantly, further proving that mh-pDMA&Zr was very stable for the selective synthesis of FOL by CTH in iPrOH.
[0169] Example 2
[0170] The method is the same as Example 1, except that 0.3 g of h-pDMA is used to prepare h-pDMA&Zr to obtain catalyst h-pDMA&Zr-2.
[0171] Example 3
[0172] The same as Example 1, the only difference is that 0.15 g of h-pDMA is taken when preparing h-pDMA&Zr to obtain catalyst h-pDMA&Zr-3.
[0173] The performance of different catalysts was tested by a method similar to that in Example 1. The results are shown in Table 3. It can be seen that if no catalyst is added during the reaction, the hydrogenation reaction is difficult to proceed and the conversion rate is 0 (serial number 1). Zirconium dioxide also shows very low reactivity (serial number 2). Using H3BTC (trimethylenediamine) and H2BDC (terephthalic acid) as organic ligands, the obtained organic metal frameworks Zr-BTC and UiO-66 show moderate reactivity, and the yields of FOL are 62.2% and 48.7% respectively (serial numbers 3 and 4). The precursor of the synthetic catalyst, h-pDMA, is also difficult to catalyze the conversion of FAL (serial number 5); when h-pDMA & Zr-2 are used as catalysts, the conversion rate of FAL is as high as 99.8%, and the yield of FOL is as high as 99.1% (serial number 6). However, pDMA&Zr prepared using solid precursor pDMA as ligand only obtained a FAL conversion rate of 69.2% and a FOL yield of 55.1% (No. 7). It is speculated that the differences in the specific surface area and pore size of the catalyst and the different adsorption effects on the substrate may be the reasons for this difference. In order to make the catalyst have magnetic recovery performance, 25 mg Fe3O4 was loaded on the surface of h-pDMA&Zr-2 (100 mg) to obtain mh-pDMA&Zr-2. When 125 mg mh-pDMA&Zr-2 was used to selectively synthesize FOL from FAL, the FAL conversion rate was 99.1% and the FOL yield was 98.2% (No. 8). Compared with h-pDMA&Zr-2, the reaction effect did not decrease significantly. It is worth noting that Fe3O4 alone cannot catalyze the formation of FOL (No. 9). Combined with the detailed characterization of the catalyst and the above experimental results, it is speculated that the presence of acidic and basic sites with appropriate content and strength in the catalyst may be the key factor for the selective generation of FOL from FAL. To further confirm the important role of acid-base sites in the hydrogenation reaction of FAL, benzoic acid and pyridine were added to the reaction system to poison the acid-base sites. In the presence of benzoic acid, the conversion of FAL and the selectivity of FOL dropped sharply, indicating that the CTH reaction catalyzed by h-pDMA&Zr-2 was closely related to the base sites on the catalyst surface (No. 10). In contrast, the addition of pyridine also reduced the conversion of FAL, but the selectivity of FOL only dropped from 99.3% to 96.3% (No. 11); 25 mg Fe3O4 was loaded on the surface of h-pDMA&Zr-1 (100 mg) to obtain mh-pDMA&Zr-1. When 125 mg of mh-pDMA&Zr-1 was used to selectively synthesize FOL from FAL, the FAL conversion rate was 54.6% and the FOL yield was 31.1% (sequence number 12); 25 mg of Fe3O4 was loaded on the surface of h-pDMA&Zr-3 (100 mg) to obtain mh-pDMA&Zr-3.When 125 mg of mh-pDMA&Zr-3 was used to selectively synthesize FOL from FAL, the FAL conversion rate was 79.0% and the FOL yield was 53.1% (No. 13). It was also found that the poisoning effect of the basic site on h-pDMA&Zr was greater than that of the acidic site on the catalyst.
[0174] Table 3 Performance test results of different catalysts a
[0175]
[0176]
[0177] aReaction conditions: 1 mmol FAL, 5 mL 2-propanol, 100 mg catalyst, 120 °C, 2 h;
[0178] b The amount of catalyst used is 125 mg;
[0179] c Add 100 mg of benzoic acid to poison the basic sites of mZr-CHPM;
[0180] d The acidic sites of mZr-CHPM were poisoned by adding 100 mg of pyridine.
[0181] Effects of reaction temperature and time on the hydrogenation of FAL to produce FOL Figures 19-20 As shown (the catalyst used is h-pDMA & Zr-2), reaction conditions: 1mmol FAL, 5mL 2-propanol, 100mg catalyst. Fig.19 It can be seen that when the temperature increases from 100℃ to 120℃, the conversion rate of FAL and the yield of FOL are significantly increased, indicating that the increase in temperature promotes the CTH reaction of FAL. When the temperature increases from 120℃ to 140℃, the conversion rate of FAL is almost unchanged, and the selectivity of FOL decreases, indicating that side reactions occur. Therefore, 120℃ is the optimal reaction temperature. The effect of reaction time on the hydrogenation of FAL to produce FOL is shown in Figure 2. Fig. 20 As shown, at 120°C, the reaction time increased from 0.5h to 2h, and the conversion rate of FAL and the yield of FOL both increased. When the reaction time was further extended to 2.5h, the conversion rate of FAL did not change significantly, but the yield of FOL decreased due to the occurrence of side reactions. The by-product was 2-(isopropyl)methylfuran. The results showed that the CTH reaction of FAL to generate FOL was the best at 120°C for 2h, with a FAL conversion rate of 99.1% and a FOL yield of 98.2%. The reaction was carried out at 120°C for 2h, and the effect of catalyst dosage (the catalyst used was h-pDMA&Zr-2) on the reaction activity was investigated. Fig.21As shown in the figure, when the catalyst dosage increases from 25 mg to 100 mg, the conversion rate of FAL and the yield of FOL both increase. When the catalyst dosage is less, due to the fewer active sites, the conversion rate of furfural and the yield of furfuryl alcohol cannot reach the best effect. The best state is achieved when the catalyst dosage is 100 mg, with a FAL conversion rate of 99.8% and a FOL yield of 99.1%. However, when the catalyst dosage is further increased to 125 mg, the selectivity of Fol is reduced due to the etherification reaction of furfural alcohol with isopropanol. Therefore, for the hydrogenation of FAL to produce FOL, a catalyst dosage of 100 mg is optimal.
[0182] like Fig. 22 As shown (the catalyst used is h-pDMA & Zr-2), reaction conditions: 1mmol FAL, 5mL alcohol, 100mg catalyst, 120℃, 2h, different alcohols also have a great influence on the selective synthesis of FOL by FAL through CTH reaction. Compared with primary alcohols (methanol, ethanol, n-propanol and n-butanol), secondary alcohols (iPrOH and sBuOH) as hydrogen donors can obtain higher FOL yields because the reduction potential of secondary alcohols is lower than that of primary alcohols. For butanol, due to the steric hindrance effect caused by its longer carbon chain, its activity is slightly lower than that of isopropanol.
[0183] Comparative Example
[0184] The performance of h-pDMA&Zr in the hydrogenation of furfural to furfuryl alcohol was compared with other different Zr-based catalysts under the following reaction conditions: 1mmol FAL, 5mL 2-propanol, 100mg catalyst. The results are shown in Table 4. At 120℃, 2h, the conversion of furfural hydrogenation catalyzed by h-pDMA&Zr was as high as 99.8%, and that of furfuryl alcohol was as high as 99.3%.
[0185] Table 4 Catalytic effect data of comparative examples and catalysts of the present invention
[0186] catalyst Temperature(℃) Time (h) Furfural conversion rate (%) Furfuryl alcohol yield (%) 1 Zr-FDCA-T 140 4 98 96 2 UiO-66 140 5 99 97 3 Zr-H3IDC 120 1 65.7 50.2 4 MOF-808 82 2 81.3 66.4 5 ZGar 140 2 98 98 6 Zr-DTPA 130 4 98.9 97.6 7 MZCCP 140 2 99.9 98.2 8 Zr-PhyA 100 2 99.3 99.3 9 Zr-LS 100 1 97.5 96 10 h-pDMA&Zr-2 120 2 99.8 99.3
[0187] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a hollow porous hydrogenation catalyst, characterized in that: The following steps are involved: The maleic anhydride, styrene, an initiator and an organic solvent are mixed to perform self-stabilizing precipitation polymerization to obtain maleic anhydride-styrene copolymer microspheres; The maleic anhydride-styrene copolymer microspheres, divinylbenzene, an initiator and an organic solvent are mixed for copolymerization growth to obtain pMS@pDMH microspheres; The pMS@pDMH microspheres are dispersed in acetone to remove the inner core and obtain hollow microspheres; dispersing the hollow microspheres in an inorganic alkaline solution for hydrolysis and saponification to obtain carboxyl functionalized microspheres; The carboxyl functionalized microspheres, soluble zirconium salt and solvent are mixed and subjected to hydrothermal reaction to obtain the hollow porous hydrogenation catalyst.
2. The preparation method according to claim 1, characterized in that: The molar ratio of maleic anhydride to styrene is 2-5:1-3.
3. The preparation method according to claim 1, characterized in that: The temperature of the self-stabilizing precipitation polymerization is 75-90° C. and the time is 1-2 hours.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the maleic anhydride-styrene copolymer microspheres to divinylbenzene is 1.5:5-10.
5. The preparation method according to claim 1, characterized in that: The copolymerization growth temperature is 75-90° C. and the time is 3-5 hours.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the carboxyl functionalized microspheres to the soluble zirconium salt is 0.15-0.6:1.5-2.
7. A hollow porous hydrogenation catalyst prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the hollow porous hydrogenation catalyst according to claim 7 in catalytic transfer hydrogenation reaction.
9. A magnetic hollow porous hydrogenation catalyst, characterized in that: Prepared by a method comprising the following steps: The amino-modified Fe3O4 nanoparticles, the hollow porous hydrogenation catalyst according to claim 7, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and a solvent are mixed and subjected to a condensation reaction to obtain the magnetic hollow porous hydrogenation catalyst.
10. Use of the magnetic hollow porous hydrogenation catalyst according to claim 9 in catalytic transfer hydrogenation reaction.